Repaglinide versus insulin for newly diagnosed diabetes in patients with cystic fibrosis: a multicentre, open-label, randomised trial. Issue 2 (February 2018) - ; Staden, Ute; Claßen, Martin; Schuster, Antje; Mellies, Uwe; Posselt, Hans-Georg; Wiebel, Matthias; Rietschel, Ernst; Stern, Martin; Teschler, Helmut; Smaczny, Christina; Köhnlein, Thomas; et al.
Summary: Background: As survival among patients with cystic fibrosis has improved in recent decades, complications have become increasingly relevant. The most frequent complication is cystic-fibrosis-related diabetes. The recommended treatment is injected insulin, but some patients are treated with oral antidiabetic drugs to ease the treatment burden. We assessed the efficacy and safety of oral antidiabetic drugs. Methods: We did a multicentre, open-label, comparative, randomised trial in 49 centres in Austria, France, Germany, and Italy. Eligible patients had cystic fibrosis, were older than 10 years, and had newly diagnosed diabetes. We used a central randomisation schedule derived from a Geigy random number table to assign patients 1:1 to receive insulin or repaglinide, stratified by sex and age (10–15 years or >15 years). The primary outcome was glycaemic control assessed by mean change in HbA1c concentration from baseline after 24 months of treatment. Differences between groups were assessed by linear models. The primary and safety analyses were done in the modified intention-to-treat population (including patients who stopped treatment early because of lack of efficacy). This trial is registered withClinicalTrials.gov, numberNCT00662714 . Findings: We enrolled 34 patients in the repaglinide group and 41 in the insulin group, of whom 30 and 37, respectively, were included in the analyses. At 24 months, glycaemic control was similar in the repaglinide and insulin groups (mean change in HbA1c concentration from baseline 0·2% [SD 0·7%], 1·7 mmol/mol [8·1 mmol/mol] with repaglinide vs −0·2% [1·3%], −2·7 mmol/mol, [14·5 mmol/mol] with insulin; mean difference between groups −0·4%, (95% CI −1·1 to 0·2 [−4·4 mmol/mol, −11·5 to 2·7], p=0·15). The most frequent adverse events were pulmonary events (43 [40%] of 107 in the repaglinide group and 60 [45%] of 133 in the insulin group), and the most frequent serious adverse events were pulmonary events leading to hospital admission (five [50%] of ten and seven [54%] of 13, respectively). Interpretation: Repaglinide for glycaemic control in patients with cystic-fibrosis-related diabetes is as efficacious and safe as insulin. Funding: Mukoviszidose eV, Vaincre la Mucoviscidose, ABCF Association, and Novo Nordisk.